Acute human orthopneumovirus infection in a captive white-handed gibbon. (May 2020) - Sojka, Peter A.; Ploog, Christina L.; Garner, Michael M.; Kiupel, Matti; Kuypers, Jane; Huynh, Thanhthao
We report herein a fatal case of acute human orthopneumovirus (formerly respiratory syncytial virus) infection in a captive white-handed gibbon ( Hylobates lar ). Other members of the housing group had mild respiratory signs. Gross examination revealed bilateral pulmonary congestion and froth in the bronchi. Microscopically, the lungs had lymphocytic, neutrophilic infiltration of the interstitium and alveolar walls. There was necrosis of terminal bronchiolar epithelium and terminal bronchioles, and surrounding alveoli contained necrotic and exfoliated epithelial cells admixed with histiocytes and syncytial cells. Additional lesions included nonsuppurative meningoencephalitis, and epidermal hyperkeratosis and hyperplasia with syncytial cell formation. PCR screening for 12 human respiratory viruses was positive for orthopneumovirus in multiple tissues, including lung, and immunohistochemical staining for human orthopneumovirus detected viral antigen within bronchial epithelial cells. IHC and PCR for measles virus on preserved sections were negative. White-handed gibbons have not been previously reported as hosts for human orthopneumovirus, an important respiratory pathogen of both primates and humans.